Comprehensive Approaches to Understanding and Managing Alzheimer’s Disease - Chandrika Kadam (International Journal of Tropical Medicines, 2024)
Alzheimer’s disease is an advanced neurodegenerative disorder described by intense memory loss. It strictly affects the patient’s quality life. The popularity of AD has been increasing in recent years. It is the most common form of mental disorder affecting more than 20 million people in the world. The Alzheimer’s disease is treated with cholinesterase inhibitors or NMDA-receptor (N-methyl D-aspartate) antagonists but here the question is about the therapeutic effect of these drugs and accordingly herbal medicine products have been used as a remedy of behavioural and psychological symptoms of dementia. The genes play major part in the progress of Alzheimer’s disease. In this article, we provided an overview that herbal medicines are useful to cure psychological disorder in elder patients. Even though there are some drugs approved by Food and Drug Administration (FDA) convenient for the treatment of AD but the outcome was not sufficient and thus the herbal medicines are the alternatives. In recent years the herbal medicines are becoming more popular, some of the herbs that is Ginseng, Ashwagandha, Brahmi, Emblica officinalis, Salvia officinalis, Uncariarhynchophylla, etc. are mentioned below. This article reviews the clinical evaluation, neuroprotective effects, anti-inflammatory effects, active constituent, mechanism of action, sedative, anxiolytic, antileprotic, antidepressant properties and health benefits of herbal medicines for the treatment of Alzheimer’s disease.
Keywords: Alzheimer's Disease; Neurodegenerative disorder; Phytomedicine; illness; psychology